Electoral Turnout of Non-Citizens Under Voluntary and Compulsory Voting: Evidence from Chile - Perez-Cosgaya, T (Cogitatio Press, 2025)
It is often argued that non-citizens are less interested in the political processes of the host country and, therefore, vote less than citizens. We discuss this using Chile’s administrative electoral census for the 2012–2023 elections. We choose Chile for three reasons. First, it is one of the few countries worldwide that allows non-citizens to vote in local and national elections. Second, Chile requires only five years of permanent residence for non-citizens to vote. Third, Chile implemented a voluntary voting system between 2012 and 2021 and a compulsory voting system in 2022. This latter particularity means that voting is compulsory for non-citizens registered on the electoral roll. How much and how did the electoral participation of citizens and non-citizens change with the introduction of compulsory voting? Four results stand out. First, citizen turnout averaged 44.7% under voluntary voting, while non-citizen turnout averaged 17.1%. Second, with the introduction of compulsory voting, the figures narrowed. Citizens averaged 86.3% and non-citizens 60.0%, tripling their turnout compared to elections organised under voluntary voting. Third, there is a gender gap in voter turnout in favour of women, both among citizens and non-citizens. Fourth, since 2020—when a constitutional referendum was held during the Covid-19 pandemic—there has been a higher turnout of young people in citizen and non-citizen groups. These results are beneficial for assessing the institutions that regulate the right and exercise of the vote for non-citizens, the impact of compulsory voting on electoral participation, and the re-boosting of youth participation. © 2025 by the author(s).